KECERDASAN EMOSIONAL DAN KECERDASAN INTELEKTUAL PENGARUHNYA TERHADAP KINERJA KARYAWAN - I Made Gita Andika; Gde Bayu Surya Parwita; Made Ika Prastyadewi (Forum Manajemen, 2017)
In the planning and development related to human resources both within the company and organizations today must get the attention of the leaders of the future that will maximize employee performance at work. Where emotional intelligence and intellect is a very important factor in improving the performance of employees and facilitate the achievement of corporate goals. If emotional intelligence and intellectual intelligence are good at a company will create a positive interaction for the development of human resources in a company or organization. The purpose of this study was to examine the emotional intelligence and the intellectual influence on employee performance. The research was conducted at PT. Bank Negara Indonesia (Persero) Tbk Main Branch Office Renon Denpasar. The sampling technique in this study using the formula Slovin, of the formula is obtained as many as 75 people. The results showed that emotional intelligence and intellect together - together (simultaneously) positive and significant influence on employee performance. Moreover, the results also revealed that emotional intelligence and intellectual intelligence partial effect on employee performance.